O tribunal penal internacional: soberania, elementos institucionais e sua implementação no Brasil - Gasparin Junior, Nelson Ricardo (2009)
The recent creation of an International Criminal Court (ICC) has generated some questions, among which pointed to the danger of being undue interference in the sovereignty of states. In this sense, the establishment of an international criminal justice can be assessed in three dimensions: the political dimension on the sovereignty of states, the legal dimension, with respect to the joint enter national law, regional and international